Does Acute Fatigue Affect Lumbar Proprioception and Balance? - Depreli, Ozde; Angin, Ender (Nova Southeastern Univ, 2023)
Purpose: To investigate the acute effects of trunk extensor, abdominal, and calf muscle fatigue on lumbar proprioception and balance. Method: Seventy healthy individuals, aged between 18-25, without pain in the low back and lower extremities, with right dominant lower extremities, were included in the study. Dynamic balance with the Y-balance Test, lumbar proprioception sense with the application of the IOS software, and fatigue level with the 6-20 Borg Scale were evaluated before and immediately after the back extensor, abdominal, and calf muscle fatigue protocols were applied to the individuals at 72-hour intervals. Results: After all fatigue protocols, proprioception sense at 30 degrees lumbar flexion was found to change significantly (p<0.05) Conclusions This study determined that acute fatigue negatively affects proprioceptive sense and dynamic postural control in the anterior direction. Understanding how the trunk extensor, abdominal, and ankle plantar flexor muscles respond to a fatigue-inducing exercise, especially concerning postural control and trunk proprioception, is important for understanding and preventing injury risk.
Keywords: fatigue; proprioception; balance; muscles